Revised and extended analysis in four times ionized xenon Xe V - Gallardo, Mario O. (1999)
The atomic-emission spectrum of four times ionized xenon (Xe V) has been observed in the region 500–6700 Å; 233 lines were classified as transition between 5s5p3, 5s25p5d, 5s25p6s with 5s25p2, 5s25p6p and 5s25p4f configurations. Ninty-seven of these lines are reported for the first time. Two new energy level values corresponding to the 5s25p4f configuration have been determined, and we proposed two new values for the previously reported 3D1 and 3G5 energy levels of this configuration. The value of the 5s25p6p 1S0 energy level has also been determined, and we propose a new value for the previously reported 5s25p5d 3F4 energy level. New adjusted values for the previously known levels of the studied configurations are included. Least-squares fitted parametric calculations involving configuration interactions have been carried out to interpret the observed spectrum.